A study on the orientation inheritance in laminated NiAl produced by in situ reaction annealing. (April 2016) - Du, Yan; Fan, Guohua; Geng, Lin
Highlights: Texture inheritance is newly found in laminated NiAl produced by reaction annealing. There is K–S orientation relationship between parent Ni and product NiAl. Interfacial characterization is used to study phase transformation in Ni–Al system. It is newly found Ni3 Al acts as pipeline between parent Ni and product NiAl. Abstract: In order to promote the performance of B2 NiAl by texture control of orientation during in situ processing, phase transformation in laminated NiAl with bimodal grain size distribution manufactured by reaction annealing of Ni and Al foils has been studied. It turned out that there existed a Kurdjumov–Sachs orientation relationship (K–S OR) between parent Ni and product NiAl by crystallography analysis according to the electron backscatter diffraction (EBSD) results. The parent Ni did not transform to the product NiAl directly but via the formation of Ni3 Al firstly according to the transmission electron microscope (TEM) observation of the interface. This led to a new K–S OR between Ni3 Al and NiAl with a small atomic misfit, which made less residual stress generated through the formation of Ni3 Al than directly from the parent Ni.